2016
DOI: 10.1016/j.jastp.2016.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Substorm probabilities are best predicted from solar wind speed

Abstract: Most measures of magnetospheric activity-including auroral power (AP), magnetotail stretching, and ring current intensity-are best predicted by solar wind-magnetosphere coupling functions which approximate the frontside magnetopause merging rate. However radiation belt fluxes are best predicted by a simpler function, namely the solar wind speed, v. Since most theories of how these high energy electrons arise are associated with repeated rapid dipolarizations such as associated with substorms, this apparent dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 55 publications
8
41
0
Order By: Relevance
“…It is clearly shown that the expansion onset occurs earlier when the solar wind velocity increases and SBZ increases. This is consistent with the statistical study showing that the integral substorm probability increases with the solar wind velocity and SBZ (Newell et al, ). The rates of change in SML for the first 10 min from the expansion onset are indicated by the numerical figures in each panel.…”
Section: Resultssupporting
confidence: 92%
“…It is clearly shown that the expansion onset occurs earlier when the solar wind velocity increases and SBZ increases. This is consistent with the statistical study showing that the integral substorm probability increases with the solar wind velocity and SBZ (Newell et al, ). The rates of change in SML for the first 10 min from the expansion onset are indicated by the numerical figures in each panel.…”
Section: Resultssupporting
confidence: 92%
“…Our model ranks V x as the second most influential factor in forecasting substorms. This is in good agreement with (Li et al., ; Luo et al., ; Newell et al., ) who showed that while the B z component of IMF plays an important role in modulating magnetospheric dynamics, the role of solar wind velocity is more important than is usually assumed. Furthermore, we confirm the result reported by Li et al.…”
Section: Discussionsupporting
confidence: 92%
“…More recently, Newell et al. () used several years of substorm onsets compiled by SuperMAG (Newell & Gjerloev, ) and showed that solar wind velocity ( V x ) could be the most important factor in driving substorms. While the growth phase of substorms was typically associated with periods of elevated solar wind driving, a few studies reported observations of substorms occurring during relatively quiet conditions (Kullen & Karlsson, ; Lee et al., ; Miyashita et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, preferential occurrence of interplanetary shocks was found in July and November (Echer et al, ). So we examine solar wind and geomagnetic conditions during the great‐FEE days using the following parameters: the solar wind speed V as the best predictor of substorm probability (e.g., Newell et al, ) and as a factor influencing interplanetary shock parameters (e.g., Lugaz et al, ); a parameter of interplanetary electric field fluctuations VδB calculated by an expression VδB = VδitalicBz2+δitalicBy2, where ()δitalicBz2 and ()δitalicBy2 are variances of the IMF B z and B y components; and AL index of substorm activity.…”
Section: Discussionmentioning
confidence: 99%